(untitled) (Sains Humanika, 2020)
Arabic language learning requires vocabulary mastery to understand reading texts. The lack of mastery may impede understanding and make it difficult for students to understand certain texts in certain fields. This study aims to analyze the words mastered by students in politics and economics. It also aims to analyze the vocabulary mastery of both fields among students. This study uses quantitative method by distributing test questions to students. The results showed that vocabulary mastery of politics and economics among students was very weak. It also showed the number of words mastered in both fields is limited. Therefore, it is proposed that the texts of political and economic fields should be included in the Arabic language syllabus as their use today is deemed necessary. Â